A Modified Subgradient Extragradient Algorithm with Inertial Effects - Komal, Somayya; Kumam, Poom (Communications in Mathematics and Applications, 2019)
In this article, we introduce an inertial modified subgradient extragradient method by combining inertial type algorithm with modified subgradient extragradient method and for solving the variational inequality (VI) in a Hilbert space \(H\). Also, we establish a weak convergence theorem for proposed algorithm. Finally, we describe the performance of our proposed algorithm with the help of numerical experiment and we show the efficiency and advantage of the inertial modified subgradient extragradient method.